Three Target Genes for the Transcriptional Activator Cat8p of Kluyveromyces lactis: Acetyl Coenzyme A Synthetase Genes KlACS1 and KlACS2 and Lactate Permease Gene KlJEN1 - Lodi, Tiziana (American Society for Microbiology, 2001)
The aerobic yeast Kluyveromyces lactis and the predominantly fermentative Saccharomyces cerevisiae share many of the genes encoding the enzymes of carbon and energy metabolism. The physiological features that distinguish the two yeasts appear to result essentially from different organization of regulatory circuits, in particular glucose repression and gluconeogenesis. We have isolated the KlCAT8 gene (a homologue of S. cerevisiae CAT8, encoding a DNA binding protein) as a multicopy suppressor of a fog1 mutation. The Fog1 protein is a homologue of the Snf1 complex components Gal83p, Sip1p, and Sip2p of S. cerevisiae. While CAT8 controls the key enzymes of gluconeogenesis in S. cerevisiae, KlCAT8 of K. lactis does not (I. Georis, J. J. Krijger, K. D. Breunig, and J. Vandenhaute, Mol. Gen. Genet. 264:193–203, 2000). We therefore examined possible targets of KlCat8p. We found that the acetyl coenzyme A synthetase genes, KlACS1 and KlACS2, were specifically regulated by KlCAT8, but very differently from the S. cerevisiae counterparts. KlACS1 was induced by acetate and lactate, while KlACS2 was induced by ethanol, both under the control of KlCAT8. Also, KlJEN1, encoding the lactate-inducible and glucose-repressible lactate permease, was found under a tight control of KlCAT8.